Perancangan Mesin Pemilah Sampah Rumah Tangga Organik dan Anorganik - Setyawan Ajie Sukarno; Sandy Bhawana Mulia; Abyanuddin Salam; Yuliadi Erdani; Kamsudin (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Manufaktur Bandung (Polman Bandung), 2023)
Waste is a real problem and will continue to increase as the human population grows. The increase in waste will have a negative impact on the environment and health if not managed properly. The process of handling household waste is still limited to collection and disposal carried out by the local Sanitation Service. In this case, recycling household waste is needed to reduce environmental impacts and improve economic and social welfare in the community. However, the problem that is often faced for this recycling process is the initial processing which includes sorting and crushing waste. This research aims to produce an efficient and appropriate household waste sorting machine design, this waste sorting machine design is useful for separating household waste that is organic and inorganic.